2014
DOI: 10.1002/wsb.446
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal relationships between deer harvest and deer-vehicle collisions at Oak Ridge Reservation, Tennessee

Abstract: White-tailed deer (Odocoileus virginianus)-vehicle collisions (DVCs) are increasing as human and deer populations continue to grow. Deer harvest was implemented at Oak Ridge Reservation, Tennessee (ORR) in 1985 to reduce DVCs. We assessed the relationship between DVCs at ORR to deer harvest, road type, and habitat features (forest, field, water, and developed cover types) during 1986-2008 using Poisson regression analysis and Akaike Information Criterion modeling. We also evaluated DVC numbers for the city of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Brief Descriptive Narrative Culling is the process of killing animals in an effort to reduce their population size because of humanwildlife conflicts, disease, or conflicts with other species (Urbanek et al 2011, Williams et al 2013, Muller et al 2014, Mawson et al 2016. In some cases, especially on islands, the objective is to not just reduce the population size of a species, but to eradicate a non-native species from the area with the goal to restore native species (Portelli andCarlile 2020, Serr et al 2020).…”
Section: Detailed Informationmentioning
confidence: 99%
“…Brief Descriptive Narrative Culling is the process of killing animals in an effort to reduce their population size because of humanwildlife conflicts, disease, or conflicts with other species (Urbanek et al 2011, Williams et al 2013, Muller et al 2014, Mawson et al 2016. In some cases, especially on islands, the objective is to not just reduce the population size of a species, but to eradicate a non-native species from the area with the goal to restore native species (Portelli andCarlile 2020, Serr et al 2020).…”
Section: Detailed Informationmentioning
confidence: 99%
“…• White-tailed deer − Statistics on deer/vehicle collisions (Muller et al 2014) − Aging techniques to determine the structure of the population (Tennessee Tech graduate student project) (Mitchell 1989) − Hunt data for sex, age, location killed, liver, bone, radioactivity levels, chronic wasting disease, Lyme disease (ticks), and abosomal parasite counts -Reptile and amphibian surveys • Remediation-effects-related research -Turtles, fish, and benthos invertebrates…”
Section: Memorandum Of Understanding Between the United States Fish And Wildlife Service Department Of The Interior And The Department Ofmentioning
confidence: 99%
“…While some indeed found that vehicles and trains collide more with deer at some particular times of the lunar cycle (e.g. full moon nights; see Colino‐Rabanal et al, 2018; Gundersen & Andreassen, 1998; Ignatavičius et al, 2021; Kawata, 2011; Steiner et al, 2021), others found no effect at all (Kreling et al, 2019; Vrkljan et al, 2020) or showed that lunar cycles were associated with collisions only at certain times of the year (Colino‐Rabanal et al, 2018; Muller et al, 2014). Finally, studies that considered multiple species found significant species‐specific differences in the effect of lunar cycles on roadkill (Mayer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%